Assessment of multi-scenario rockfall hazard based on mechanical parameters using high-resolution airborne laser scanning data and GIS in a tropical area - Fanos, Ali Mutar; Pradhan, Biswajeet; Abdul Aziz, Azlan; Jebur, Mustafa Neamah; Hyuck, Jin Park (Springer Verlag, 2016)
Rockfall hazard is a main threat for mountainous and hilly areas that can cause loss of life, damage to infrastructures, and traffic interruption. Rockfall frequency and magnitude vary both spatially and temporally; therefore, multi-scenarios related to rockfall characteristics (trajectories, frequency and kinetic energy) can provide early warnings by identifying the areas at risk for mitigation purposes. The aim of this study is to predict the areas at risk from future rockfall incidents and suggest suitable mitigation measures to prevent them. The most significant elements in rockfall analysis are slope topography interpretation or the digital elevation model (DEM) and the rockfall modeling approach. Light detection and ranging (LiDAR) techniques have been widely used in rockfall studies because of their capability to provide high-resolution information regarding slope surfaces. In the current study, airborne laser scanning (ALS) is used to obtain a high-density point cloud (4 pts./m2) of the study area for the construction of an accurate DEM via a geographic information system. Rockfall source areas were identified based on multi-criteria method including DEM derivatives (e.g., slope, aspect, curvature and topographic contrast) in addition to terrain type and aerial photos. A 3D rockfall model has been established to determine rockfall multi-scenarios based on their characteristics according to a range of restitution coefficient (normal and tangential) and friction angle values; these parameters are particularly crucial in rockfall simulation to delineate the spatial prediction of rockfall hazard areas along the Jelapang corridor of the North–South Expressway in Malaysia. In addition, a barrier location was suggested based on limited rockfall height and kinetic energy to mitigate rockfall hazards. Results show that rockfall trajectories (stopping distance) and, subsequently, their frequency and energy are increased; moreover, barrier efficiency is reduced when the values of the mechanical parameters (Rn, Rt, and friction angle) are increased. Nonetheless, the suggested barrier location is an efficient and mitigative measure to eliminate the rockfall effect.